DEMPLOT PENANAMAN SEMANGGI DENGAN FORMULA ORGANIK CAIR DI LAHAN KERING - Adi Budiwan; Dwiyana Anela Kursniasari; Heri Susanto (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Semanggi Village, RW 3, Kendung Sememi, Surabaya, grows clover all year round. When there is a long dry season with the possibility of death, with the irrigation treatment using an organic formula it is expected to be able to increase the planting period and even grow better and produce maximum results. The clover field demonstration plot is evidence that will provide solutions in optimal and environmentally friendly clover cultivation. The method of activities carried out in this demonstration plot includes lectures on: how to cultivate clover in dry land, how to provide the right fertilizer for clover through the application of liquid organic formulas and how to use vegetable pesticides. Preparation for Implementation, The demonstration plot for clover cultivation in dry land is only a plot of land available with complete facilities. The tools used are only those that are necessary so that the demonstration plot process is not complicated. The physical yield of clover is quite satisfactory in the sense that the leaves are wide enough (quality), and will automatically increase the volume of weight in terms of weight (quantity)